ASSA13-10-14 Cellular Repressor of E1A-Stimulated Genes Accelerates Endothelial Angiogenesis Via Integrin-Linked Kinase-PINCH-CDC42 Activation. (29th April 2013) - Jie, Tao; Chenghui, Yan; Huimin, Zhang; Xiaoxiang, Tian; Yang, Li; Jian, Zhang; Mingyu, Sun; Shaohua, Li; Yaling, Han
Abstract : Background: Cellular repressor of E1A-stimulated genes (CREG) is an important endothelial-protective gene, which is reported to modulate the mobility of endothelial cells. Objective: The study aimed to investigate the effects of CREG on endothelial angiogenesis. Methods: Aortic expression of CREG protein was detected by western blot and immnuostaining in CREG heterozygous (CREG +/- ) mice and wild-type littermates. Perfusion recovery of hind limb was valued by laser Doppler in mice and wild-type littermates 14 days after the hind limb arterial ligation. The matrigel experiments in vivo and in vitro were performed after the human umbilical vein endothelial cells (HUVEC) were infected by adenovirus overexpressing CREG or adenovirus expressing GFP as control, and the filopodium formation was observed to evaluate the CREG function on neovascularization. Different integrin-linked kinase (ILK) subunit site mutant plasmids and small interfering RNA identified p-Cdc42 were transfected into HUVEC to explore the mechanism through which CREG-mediated endothelial angiogenesis. Results: Aortic expression of CREG protein was detected to reduce remarkably in CREG +/- mice compared to that in wild-type littermates. Meanwhile, laser Doppler perfusion imaging showed that perfusion recovery was significantly impaired in CREG +/- mice than that in wild-type littermates after 14 days hind limb arterial ligation (78.23 ± 7.2% vs 12.15 ± 2.058% in calf; 58.23 ± 6.5% vs 32.15 ± 3. 514% in thigh; P < 0.001). Subsequently, overexpression of CREG in HUVEC increased endothelial cell network formation in vitro, enhanced neovascularization and improved limb perfusion in vivo, accompanied by filopodium formation and changes in cell shape. Mechanismly, integrin-linked kinase (ILK), a key adhesion plaque protein, participated in CREG-mediated endothelial angiogenesis. Furthermore, studies using small interfering RNA identified p-Cdc42 to be a key downstream molecule of ILK involved in CREG-mediated endothelial cell filopodium formation. Transfection with binding-site-mutant plasmids of ILK and co-immunoprecipitation revealed that CREG activated the ILK-PINCH complex, which is involved in the regulation of p-Cdc42 activation. Conclusions: CREG overexpression stimulates the endothelial filopodium formation and regulates angiogenesis via the ILK/PINCH/p-Cdc42 signalling pathway, which provides the basis for future studies in the field of angiogenesis.